Tono-pen measurement of intraocular pressure under topical anaesthesia in full term normal newborns Running title:Intraocular pressure in newborns - Sagili Chandrasekhara Reddy; Rosnita Alias (International Journal of Ophthalmology, 2014)
AIM: Tono-pen measurement of intraocular pressure (IOP) under topical anaesthesia in full term normal newborns.METHODS: The IOP measurements were taken using Tono-pen XL tonometer under topical anaesthesia in 150 newborns (300 eyes) within 24h after birth, over a period of three months, in a university hospital. Gender, gestation period, mode of delivery and birth weight of newborns were noted from medical records.RESULTS:There were 70 males and 80 females. All babies were Malays. The IOP measurements were taken between 12 and 24h after birth. The gestation period of babies ranged between 37 and 41 weeks; 118 babies were delivered by spontaneous vaginal delivery and 32 by caesarian section. The birth weight of babies ranged between 2.1 and 4.3kg. The mean IOP of 300 eyes was 15.99±2.79mmHg (range 8-22). There was no statistically significant difference of mean IOP and gender, laterality of eye, type of delivery, gestation age, or birth weight of newborns.CONCLUSION: The IOP in full term normal newborns was 16mmHg. Tono-Pen appears to be ideal instrument for taking IOP in newborns because of its small size and easy handling.